2013
DOI: 10.1016/j.matdes.2012.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and glass hierarchical fibers: Influence of carbon nanotubes on tensile, flexural and impact properties of short fiber reinforced composites

Abstract: a b s t r a c tDense carbon nanotubes (CNTs) were grown uniformly on the surface of carbon fibers and glass fibers to create hierarchical fibers by use of floating catalyst chemical vapor deposition. Morphologies of the CNTs were investigated using scanning electronic microscope (SEM) and transmission electron microscope (TEM). Larger diameter dimension and distinct growing mechanism of nanotubes on glass fiber were revealed. Short carbon and glass fiber reinforced polypropylene composites were fabricated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(83 citation statements)
references
References 31 publications
8
75
0
Order By: Relevance
“…It is confirmed that the CNT grafting onto carbon fiber is effective to modify IFSS of carbon fiber/polypropylene systems, though the penetration and wettability of polypropylene to grafted fibers were concerned. In this study, the thickness of CNT layer was less than 1µm, and thinner compared to other researches [12,15]. In the case of thin CNT layer, polypropylene can penetrate between CNT, and thus improve IFSS by mechanical interlocking effect of CNT.…”
Section: Single Fiber Tensile Testsmentioning
confidence: 66%
See 2 more Smart Citations
“…It is confirmed that the CNT grafting onto carbon fiber is effective to modify IFSS of carbon fiber/polypropylene systems, though the penetration and wettability of polypropylene to grafted fibers were concerned. In this study, the thickness of CNT layer was less than 1µm, and thinner compared to other researches [12,15]. In the case of thin CNT layer, polypropylene can penetrate between CNT, and thus improve IFSS by mechanical interlocking effect of CNT.…”
Section: Single Fiber Tensile Testsmentioning
confidence: 66%
“…Vishkaei et al [14] and Rahmanian et al [15] confirmed approximately 40% and 30% enhancement in tensile strength and stiffness compared to conventional SFRP, respectively. They concluded that in addition to causing enhanced fiber-matrix interfaced bonding, CNT also act as reinforcement.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several researches have been reported on impregnation of CNTs into carbon fibers (CFs): infusion/impregnation of a CNT-resin mixture into the primary fiber assembly [8,9], direct growth of CNTs on reinforcement fiber surface through chemical vapor deposition (CVD) [10,11], direct placement of CNTs between layers of the preform [12], electrophoretic deposition onto the surface of fiber [13,14], electrostatic assembly of oxidized CNTs onto functionalized fiber [15] and coating of fiber with CNT-containing sizings [16][17][18][19][20]. Especially, the first and the third methods are widely used due to the easiness of application.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Polymers reinforced with nanosized fillers are promising candidates for various applications requiring lightweight, high-performance, and multifunctional materials. To date, pristine clays, 12 organically modified clays, 13,14 nanofibers, 15 whiskers, 16 or more recently carbonaceous fillers 3,17,18 have received much more attention. Among conventional nanofillers, both carbon nanotubes (CNTs) and graphene have exceptional electric transport, thermal and mechanical properties, which appear as excellent candidates to make advanced functional composite materials.…”
Section: Introductionmentioning
confidence: 99%